Determination of Ibuprofen content in tablets using Raman spectroscopy - Bui, Bao Duy; Ho, Manh Khanh; Le, Thi Bao Tram; Dao, Thi Cam Minh (Tạp chí Y Dược Huế, 2025)
Background: Raman spectroscopy has emerged as a powerful analytical technique widely applied across various research fields due to its rapid, non-destructive nature. This study was conducted to explore the applicability of Raman spectroscopy in the quantitative analysis of pharmaceutical formulations and to contribute to the optimization of quality control processes during tablet manufacturing. Materials and Methods: Ibuprofen tablets with varying active ingredient contents were prepared to investigate their Raman spectral profiles. Chemometric approaches were applied to develop quantitative calibration models. The analytical method was validated in accordance with ICH and AOAC guidelines. Results: Spectral acquisition was performed over the range of 150 cm-1 to 2800 cm-1, yielding distinct characteristic peaks. The optimal measurement conditions included intensity-based signal acquisition with an integration time of 27 seconds. The developed Raman method demonstrated high specificity, linearity, and accuracy within the concentration range of 32.4% to 48.6% w/w of Ibuprofen in tablets. Comparative analysis between the Raman and HPLC methods showed no statistically significant difference in quantification results. Conclusion: A reliable and validated Raman spectroscopic method was successfully developed for the quantification of Ibuprofen in 200 mg tablet formulations. The results obtained were consistent with those of the HPLC method described in the Vietnamese Pharmacopoeia, Edition V, confirming the potential of Raman spectroscopy as an alternative analytical tool for routine quality control